Population Using Tobacco for Pain Relief: A Preliminary Cross‐Sectional Study in Japan - Keiko Yamada; Satoko Chiba; Masako Iseki; Takahiro Tabuchi (Neuropsychopharmacology Reports)
ABSTRACT Background There is a complex relationship between tobacco use and pain. Nicotine provides temporary pain relief but increases the risk of chronic pain. This study aimed to investigate use of tobacco for pain relief and its association with demographic and medical characteristics in Japan. Methods We used a web‐based survey to recruit 2000 individuals aged 20–69 who had experienced pain in the previous month. They answered questions on demographics, smoking status, lifestyle, socioeconomic status, and medical information. Smokers were asked if they smoked tobacco to relieve pain. Those who responded “strongly agree” or “agree” were labeled as using tobacco for pain relief. We used analysis of covariance to test the associations among smokers' background characteristics by whether they used tobacco for pain relief. Results Overall, 6.6% of smokers with pain (3.5% with acute or subacute pain and 8.8% with chronic pain) used tobacco for pain relief. These individuals were generally younger, more likely to be treated for schizophrenia and use analgesics, with higher pain severity, more catastrophic thinking about pain, and a centralized symptom. However, they were less likely to engage in regular exercise. Conclusions Overall, 6.6% of smokers (3.5% with acute or subacute pain and 8.8% with chronic pain) used tobacco to relieve their pain, even though most of them also received medical treatment and used pain medication. Healthcare providers and policy makers should account for this population of smokers in their planning.